Model Ekonomi Minyak Sawit Mentah Dunia - Wayan R. Susila; Bahtiar S. Abbas; Prayogo U. Hadi; Arief Priyambodo; S. Oloan Lubis (Jurnal Agro Ekonomi, 1995)
Due to the importance of crude palm oil (CPO) in Indonesia economy, any policy elated to CPO industry should be comprehensively designed and analyzed its impacts on the industry and the economy as a whole. A scientific approach to designed and analyze policies is by simulating those policies into an economic model of the industry. In response to requirement, a study has been conducted to develop an international model of crude palm oil market. The model consists of 18 sub-models, that are, a world model, 16 individual or grouped country models, and an Indonesia model which is specified in relatively more detail. A general characteristic of the model is that the shot-term responses of production, consumption, export, and import toward the changes in CPO and competing oil prices are inelastic. Using the model and a time horizon of 1995-2000, production, consumption, export-import are projected to increase by 6.1, 5.0, and 4.1, percent, p.a., respectively. The price is projected to decline to be around US$ 415/ton in 2000